What's new in bone and soft tissue pathology 2023: guidelines for molecular testing - Farres Obeidin (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Our understanding of bone and soft tissue tumors has thoroughly evolved as a consequence of modern molecular techniques. DNA and RNA sequencing methods play an important diagnostic and therapeutic role in sarcoma pathology. Herein, we discuss current guidelines and best practices for molecular testing in bone and soft tissue tumors.